UPACARA TEING NGASANG DALAM TRADISI MASYARAKAT MANGGARAI DAN SAKRAMEN BAPTIS (Sebuah Pengantar Studi Perbandingan Inisiasi) - Jagom, Bonifasius (Fides et Ratio : Jurnal Teologi Kontekstual Seminari Tinggi St. Fransiskus Xaverius Ambon, 2020)
For the etnic society of Manngarai, West Folres, the presence of child/baby in their family is a gift from God that must be grateful. The thanksgiving ceremony for the presence of the child is called Teing Ngasang. Teing Ngasang is a rite of giving a name to a child who born into the Manggarai people. For the name is something very valuable. Name is a representation of a person's personality. The "name" actually includes one's identity and behavior patterns. Therefore, Manggarai people always try to avoid actions or behavior that can damage their reputation. The author's focus is to look at the comparison of initiation rites as well as points of equality and difference between the ceremony of Teing Ngasang and Baptist Sacrament in the Catholic Church. In addition, the author will review the points which are donations from the Teing Ngasang ceremony in relation to the Baptist Sacrament. The findings of this comparative study are a change in the meaning of the Teing Ngasang ceremony in the light of Christian Faith. In addition, it is also known that the relations and the awareness of the Supreme Being in the lives of the Manggarai people existed long before Catholicism entered.